Characteristics of primary care practices by proportion of patients unvaccinated against SARS-CoV-2: a cross-sectional cohort study - Shuldiner, Jennifer; Green, Michael E.; Kiran, Tara; Khan, Shahriar; Frymire, Eliot; Moineddin, Rahim; Kerr, Meghan; Tadrous, Mina; Nowak, Dominik Alex; Kwong, Jeffrey C.; Hu, Jia; Witteman, Holly O.; et al. (Canadian Medical Association Journal, 2024)
Background: Variations in primary care practices may explain some differences in health outcomes during the COVID-19 pandemic. We sought to evaluate the characteristics of primary care practices by the proportion of patients unvaccinated against SARS-CoV-2.Methods: We conducted a population-based, cross-sectional cohort study using linked administrative data sets in Ontario, Canada. We calculated the percentage of patients unvaccinated against SARS-CoV-2 enrolled with each comprehensive-care family physician, ranked physicians according to the proportion of patients unvaccinated, and identified physicians in the top 10% (v. the other 90%). We compared characteristics of family physicians and their patients in these 2 groups using standardized differences.Results: We analyzed 9060 family physicians with 10 837 909 enrolled patients. Family physicians with the largest proportion (top 10%) of unvaccinated patients (n = 906) were more likely to be male, to have trained outside of Canada, to be older, and to work in an enhanced fee-for-service model than those in the remaining 90%. Vaccine coverage (≥ 2 doses of SARS-CoV-2 vaccine) was 74% among patients of physicians with the largest proportion of unvaccinated patients, compared with 87% in the remaining patient population. Patients in the top 10% group tended to be younger and live in areas with higher levels of ethnic diversity and immigration and lower incomes.Interpretation: Primary care practices with the largest proportion of patients unvaccinated against SARS-CoV-2 served marginalized communities and were less likely to use team-based care models. These findings can guide resource planning and help tailor interventions to integrate public health priorities within primary care practices.